Bringing Things Back from Nothingness: The Restoration of the Non-Existent before and after Avicenna - Francesco Omar Zamboni (Nazariyat: Journal for the History of Islamic Philosophy and Sciences, 2022)
This paper presents the evolution of the Islamic debates on i‘ādat al-ma‘dūm [restoration of the non-existent], examining the notion itself, the motives behind its adoption and rejection, and the arguments for and against its possibility. Restoration consists in an act of recreating a previously annihilated entity while preserving its identity. Most pre-Avicennian theologians accept the possibility of restoration, while disagreeing on one preliminary issue (the reality of the non-existent) and one derivative issue (the restorability of specific classes of entities). Adopting restoration enabled the mutakallimūn to reconcile a corporealist anthropology with the possibility of resurrection. Avicenna presented an influential case against the possibility of restoration consisting of three main arguments: from intuition (in light of the unreality of the non-existent), from the indiscernibility of a restored entity from its equivalent copy, and from the contradiction entailed by the restoration of time. Among the post-Avicennian schools, only the Ash‘arites defended the possibility of restoration. The debates of the post-Classical period built upon the basic argumentative core outlined by Avicenna and the early Mutakallimūn, considering more sophisticated formulations (the argument from modal invariance), objections, and answers, as well as designing some totally new arguments both for (from the possibility of the conceptual parts, from remembrance, from presumptive possibility) and against restoration (from intermittence, from the restoration of the causal factors).